DISEMINASI TEKNOLOGI SEDERHANA BUDIDAYA TERIPANG PASIR (SEA CUCUMBER) SISTEM PEN CULTURE SEBAGAI UPAYA MENGATASI ANCAMAN PENANGKAPAN BERLEBIHAN - Reniati; Bidayani, Endang; Priyambada, Agung (Program Studi Budidaya Perairan Universitas Mataram, 2022)
The sea cucumber with the Latin name Holothuria scabra has high economic value. This leads to overfishing in nature. One of the areas in the Bangka Belitung Islands Province that produces sand sea cucumbers is the Coastal Village of Batu Aer, Simpang Pesak District, East Belitung Regency. The problems faced by partners at this time are: 1) Partners do not have the skills to manage the sea cucumber cultivation business, because they still catch from nature; and 2) Partners do not have knowledge related to sea cucumber cultivation technology. This activity is expected to contribute, among others: 1) Helping traditional fishermen to get a side business from sea cucumber cultivation; and 2) Increasing the income of traditional fishermen from sea cucumber cultivation. The outputs resulting from this activity are: 1) Increasing the quantity and quality of cultivation products; 2) Improving community understanding and skills for sea cucumber cultivation; and 3) Increasing people's income.